Vibration control in buildings under seismic excitation using optimized tuned mass dampers (Fracture and Structural Integrity, 2020)
Earthquakes can cause vibration problems in many types of structures, generating large displacements. The interstory drift is a design criterion very used in seismic analysis and the structural control is an alternative to reduce these displacements and improve the performance of these structures adapting them to the imposed criteria. TMD is a device widely used due to the simple principle of operation and many successful applications in real life practice. This paper investigates the use of optimized TMD for reduction of maximum horizontal displacement at the top floor and interstory drift of a steel building under seismic excitation considering three scenarios: single TMD at the top floor; MTMD horizontally arranged at the top floor; and MTMD vertically arranged on the structure. By a metaheuristic optimization algorithm, the parameters and positions of the devices are obtained. Three real and one artificial earthquakes are employed in the simulations. The results showed that all proposed scenarios are efficient in reducing top floor response and interstory drift to values below of the interstory drift limits allowed by the standard code consulted. However, Scenario 2 presented the best reduction for the top displacement and interstory drift to the critical floor for the worst earthquake considered.
Keywords: TMD; Vibration control; Optimization; Whale Optimization Algorithm; Interstory drift